The act of refuge : facilitating spatial practices of mobile dweller in the city of Pretoria - Barker, A.A.J. (Arthur Adrian Johnson) (University of Pretoria, 2022)
Mini Dissertation (MArch (Prof))--University of Pretoria 2021.